Capturing complexity: Forests, decision-making and climate change mitigation action. (September 2018) - Klapwijk, M.J.; Boberg, J.; Bergh, J.; Bishop, K.; Björkman, C.; Ellison, D.; Felton, A.; Lidskog, R.; Lundmark, T.; Keskitalo, E.C.H.; Sonesson, J.; Nordin, A.; et al.
Graphical abstract: Highlights: Implementation of forest-derived climate change mitigation is hampered by complexity within socio-ecological systems. We capture this complexity by four components to decision-making: cognitive, institutional, strategic, and normative. A conceptual figure is developed to visualize the main obstacles and to facilitate decision-making pathways. Further research on these complex issues is needed focusing on the interactions between obstacles in each component. Abstract: Managed forests can play an important role in climate change mitigation due to their capacity to sequester carbon. However, it has proven difficult to harness their full potential for climate change mitigation. Managed forests are often referred to as socio-ecological systems as the human dimension is an integral part of the system. When attempting to change systems that are influenced by factors such as collective knowledge, social organization, understanding of the situation and values represented in society, initial intentions often shift due to the complexity of political, social and scientific interactions. Currently, the scientific literature is dispersed over the different factors related to the socio-ecological system. To examine the level of dispersion and to obtain a holistic view, we review climate change mitigation in the context of Swedish forest research. We introduce a heuristic framework to understand decision-making connected to climate change mitigation. We apply our framework to two themes which span different dimensions in the socio-ecological system: carbon accounting and bioenergy. A key finding in the literature was the perception that current uncertainties regarding the reliability of different methods of carbon accounting inhibits international agreement on the use of forests for climate change mitigation. This feeds into a strategic obstacle affecting the willingness of individual countries to implement forest-related carbon emission reduction policies. Decisions on the utilization of forests for bioenergy are impeded by a lack of knowledge regarding the resultant biophysical and social consequences. This interacts negatively with the development of institutional incentives regarding the production of bioenergy using forest products. Normative disagreement about acceptable forest use further affects these scientific discussions and therefore is an over-arching influence on decision-making. With our framework, we capture this complexity and make obstacles to decision-making more transparent to enable their more effective resolution. We have identified the main research areas concerned with the use of managed forest in climate change mitigation and the obstacles that are connected to decision making.